2014
DOI: 10.1186/1471-2407-14-760
|View full text |Cite
|
Sign up to set email alerts
|

GLUT-1 expression is largely unrelated to both hypoxia and the Warburg phenotype in squamous cell carcinomas of the vulva

Abstract: BackgroundStrongly increased uptake of glucose is a hallmark of solid malignant tumors. This phenotype can be triggered by hypoxia-induced gene expression changes or can occur independently of hypoxia as a consequence of malignant transformation itself, and is often referred to as the Warburg effect. The glycolytic phenotype has been associated with malignant progression and resistance to radio- and chemotherapy.MethodsWe have chosen squamous cell carcinomas of the vulva (SCC-V) as a representative solid tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…In striking contrast to normal cells, cancer cells preferentially uptake and convert glucose into lactate even in the presence of sufficient oxygen [ 29 ]. This seemingly “inefficient” metabolic characteristic relies largely on aberrant upregulation of GLUT1, a glucose transporters abundantly expressed in cancer cells [ 30 , 31 ], although one contradictory study reported that GLUT1 is not necessarily involved in the Warburg effect depending on the degree of tumor invasiveness [ 32 ]. Inefficient ATP synthesis becomes an obstacle for cancer cells only when their energy resources are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In striking contrast to normal cells, cancer cells preferentially uptake and convert glucose into lactate even in the presence of sufficient oxygen [ 29 ]. This seemingly “inefficient” metabolic characteristic relies largely on aberrant upregulation of GLUT1, a glucose transporters abundantly expressed in cancer cells [ 30 , 31 ], although one contradictory study reported that GLUT1 is not necessarily involved in the Warburg effect depending on the degree of tumor invasiveness [ 32 ]. Inefficient ATP synthesis becomes an obstacle for cancer cells only when their energy resources are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pimonidazole, administered exogenously and successively stained, is also considered a useful marker for the identification of low-oxygen environments [9]. Some studies, however, indicate that the expression of CA9 and GLUT-1 varies in different cancer cell lines [10, 11]. Additionally, immunohistochemistry for these markers in relation to pimonidazole staining has yielded conflicting results [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously showed that high expression of VEGF, GLUT-1, p53, markers of angiogenesis [ 16 ], tumour metabolism [ 17 ] and tumour proliferation [ 18 , 19 ], and low expression of ER, are predictors of response to epirubicin. Among these, the role of GLUT-1 is still controversial, in fact it is unknown whether GLUT-1 is associated to hypoxia in breast cancer cells or it is a hypoxia-independent feature of transformed cells which display altered metabolism, as in other cancers [ 20 ]. Therefore, the discrepancy between the expression of hypoxia-markers and the rate of response to anthracyclines/DFS/OS that we found in this study could be explained by the fact that GLUT-1 is perhaps expressed in breast cells irrespective of the degree of hypoxia, or independently from it.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the discrepancy between the expression of hypoxia-markers and the rate of response to anthracyclines/DFS/OS that we found in this study could be explained by the fact that GLUT-1 is perhaps expressed in breast cells irrespective of the degree of hypoxia, or independently from it. A recent report demonstrated a requirement for GLUT-1 in mammary tumourigenesis [ 20 , 21 ] as a consequence of the fact that early malignant transformation requires glucose. The metabolic alterations typically found in tumour cells, more than the response to hypoxia, could explain our results.…”
Section: Discussionmentioning
confidence: 99%